2022
DOI: 10.1007/s00167-022-07042-y
|View full text |Cite
|
Sign up to set email alerts
|

Hip arthroscopy for femoroacetabular impingement is associated with significant improvement in early patient reported outcomes: analysis of 4963 cases from the UK non-arthroplasty registry (NAHR) dataset

Abstract: Purpose Results from recent randomised controlled trials demonstrate the superiority of surgery over physiotherapy in patients with femoroacetabular impingement (FAI) of the hip in early follow-up. However, there is paucity of evidence regarding which factors influence outcomes of FAI surgery, particularly notable is the lack of information on the effect of impingement subtype (cam or pincer or mixed) on patient reported outcomes measures (PROMs). This study aims to evaluate the early outcomes of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 66 publications
0
9
0
Order By: Relevance
“…Concomitant with these increases in the use of hip preservation surgery, there has been a rapid increase in the volume of related data and literature. A hip arthroscopy registry was commenced by a Scandinavian expert group in 2011 [25], and the following year the NAHR was founded in the United Kingdom (UK) [11]. There has been a dramatic increase in the number of publications on topics related to hip preservation surgery, though the quality of these studies continues to be low, with the majority of studies providing Level IV evidence [16].…”
Section: The Evolution Of Hip Preservation and Hip Arthroscopymentioning
confidence: 99%
See 1 more Smart Citation
“…Concomitant with these increases in the use of hip preservation surgery, there has been a rapid increase in the volume of related data and literature. A hip arthroscopy registry was commenced by a Scandinavian expert group in 2011 [25], and the following year the NAHR was founded in the United Kingdom (UK) [11]. There has been a dramatic increase in the number of publications on topics related to hip preservation surgery, though the quality of these studies continues to be low, with the majority of studies providing Level IV evidence [16].…”
Section: The Evolution Of Hip Preservation and Hip Arthroscopymentioning
confidence: 99%
“…Amongst patients undergoing hip arthroscopy for FAI, there is significant improvement of patient‐reported outcomes (PROMs) at 6 and 12 months post‐operatively compared to baseline. Pre‐operatively, and at 12 months post‐operatively, PROMs were significantly lower in patients with pincer morphology compared to cam and mixed types [11].…”
Section: Patient Demographicsmentioning
confidence: 99%
“…Excision of the impingement lesion (Cam, pincer or mixed) and addressing chondro-labral pathology through surgical procedures like hip arthroscopy may be necessary to provide better medium to long term outcomes [ 8 ]. Innovations in diagnosis and surgical technique have resulted in an exponential growth of hip arthroscopy procedures in the past decade [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Non-Arthroplasty Hip Registry from the UK also showed that only 67% of patients achieved the minimal clinically important difference (MCID) on the iHOT-12 scale in the short term following arthroscopic treatment for FAI. 13 However, there is contradictory evidence on the outcomes of HA in patients with moderate-to-severe OA. 14 It is also not clear how the location and degree of chondral damage affects the outcome.…”
Section: Introductionmentioning
confidence: 99%
“…The Non-Arthroplasty Hip Registry from the UK also showed that only 67% of patients achieved the minimal clinically important difference (MCID) on the iHOT-12 scale in the short term following arthroscopic treatment for FAI. 13…”
Section: Introductionmentioning
confidence: 99%